Reputation: 287
I am trying to write a Haskell code which takes in a list and return a list of list. When I do that as the following code, I am getting "non-exhaustive patterns in function reGroup"
reGroup :: [[Int]] -> [Int] -> [[Int]]
reGroup [[]] [] = [[]]
reGroup [[]] xs = reGroup [(take 3 xs)] (drop 3 xs)
reGroup [[a]] [] = [[a]]
reGroup [[a]] xs = reGroup [[a], (take 3 xs)] (drop 3 xs)
-- calling the reGroup function from another function as follow
reGroup [[]] [1,2,3,4,5,6,7,8,9]
What i want is [1,2,3,4,5,6,7,8,9]
-> [[1,2,3], [4,5,6], [7,8,9]]
. What am I doing wrong or can someone show me an easy way to it?
Upvotes: 0
Views: 824
Reputation: 28539
It is probably easier to try to do this without the accumulator (the first argument). Then we would have
groupThree :: [a] -> [[a]] --why only work with Ints?
--if the list begins with three elements, stick them in a group
--then group the remainder of the list
groupThree (a:b:c:more) = [a,b,c]:groupThree more
--grouping an empty list gives you an empty list
groupThree [] = []
--if we have some number of elements less than three
--we can just stick them in a list
groupThree other = [other]
Or using drop and take
groupThree :: [a] -> [[a]]
groupThree [] = []
groupThree ls = (take 3 ls):groupThree (drop 3 ls)
which does exactly the same thing.
The reason your code does not work is that
reGroup [xs,ls] y
does not match with any of your cases--you only have code to handle the first argument being a list of exactly one element, that element being the empty list or a list with exactly one element.
The correct use of an accumulator would be
reGroup back [] = back
reGroup back ls = reGroup (back ++ [take 3 ls]) (drop 3 ls)
unfortunately, this is very inefficient since you are appending to the end of a list (taking time proportional to the length of that list...modulo lazieness). Instead, you should use
reGroup back [] = reverse back
reGroup back ls = reGroup ((take 3 ls):back) (drop 3 ls)
although I like the version without an accumulator better since it is lazier (and so can handle infinite lists).
Upvotes: 7
Reputation: 8103
take3 :: [a] -> [[a]]
take3 [] = []
take3 (x:[]) = [[x]]
take3 (x:y:[]) = [[x,y]]
take3 (x:y:z:xs) = [[x,y,z]] ++ take3 xs
Upvotes: 0
Reputation: 3028
Changing your code a little to this
reGroup :: [[Int]] -> [Int] -> [[Int]];
reGroup [[]] [] = [];
reGroup a [] = a;
reGroup [[]] xs = reGroup [(take 3 xs)] (drop 3 xs);
reGroup a xs = a ++ reGroup [(take 3 xs)] (drop 3 xs);
does the job.
Upvotes: 1
Reputation: 796
[[a]]
is only a list with a list with one element, like [[1]].
So after one recursion you get from
reGroup [[]] [1,2,3,4,5,6,7,8,9]
to
reGroup [[1,2,3]] [4,5,6,7,8,9]
but for this case (a list with a list with 3 elements) is no pattern defined.
Upvotes: 4
Reputation: 1705
Try this:
reGroup xs n =
if drop n xs == []
then [take n xs]
else [take n xs] ++ (reGroup (drop n xs) n)
Probably not the most efficient, but it's a start.
It outputs:
> reGroup [1..9]
[[1,2,3],[4,5,6],[7,8,9]]
> reGroup [1..10]
[[1,2,3],[4,5,6],[7,8,9],[10]]
And the reason you're getting that error is because you haven't covered all the patterns the function can match. Try throwing in a _
or two for your base case(s).
Upvotes: 2